High-weather-resistance textile material and preparation method thereof
By blending aging-resistant serole fiber with flame-retardant modified polyester fiber, combined with nano zinc oxide and nitrogen-phosphorus flame retardant, the problem of aging of textile materials in sunlight ultraviolet radiation and humid and heat environments is solved, and the high weather resistance of textile materials is achieved, which significantly improves service life and safety.
Patent Information
- Application Number
- CN202411573707.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-28
AI Technical Summary
Textile materials age in sunlight ultraviolet radiation and humid and heat environments, resulting in color fading, reduced intensity, unstable size, and prone to breeding bacteria and molds. They also lack anti-static and flame retardant properties and have short service life.
Aging-resistant syringe fibers are blended with flame-retardant modified polyester fibers, and aging-resistant syringe fibers are prepared by reacting modified syringe fibers with vanillic acid, and flame-retardant modified polyester fibers are produced by melt spinning. Combined with nano zinc oxide and nitrogen-phosphorus flame retardant, a textile material with excellent anti-ultraviolet, anti-aging, flame-retardant and antibacterial properties are formed.
Significantly improve the service life of textile materials, enhance their anti-ultraviolet, anti-aging, flame retardant and antibacterial properties, and improve their use safety and storage stability.
Smart Images

Figure CN119711169A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile materials, and in particular to a highly weather-resistant textile material and a preparation method thereof. Background Art
[0002] Textiles are indispensable materials in people's daily life and production. From home decoration to outdoor equipment, from clothing and accessories to industrial applications, textile materials play a vital role. However, the weather resistance of textile materials has always been one of the key factors affecting their service life and function, especially under the ultraviolet radiation of sunlight and the oxidation effect in a hot and humid environment. The surface temperature of textile materials rises under long-term sunlight, and ultraviolet rays penetrate the fiber, destroying the fiber molecular structure and accelerating the aging process, which will not only cause the color of the textiles to fade but also reduce the strength. In a hot and humid environment, textile materials easily absorb moisture in the air, causing the fibers to swell and soften, affecting the dimensional stability and reducing the strength and durability of the fibers. At the same time, in a hot and humid environment, it is easy to breed bacteria and mold, causing biological corrosion to the textile materials, further shortening their service life.
[0003] In addition, textile materials easily generate static electricity when rubbed or touched, which affects the wearing comfort when making clothes. The accumulation of static electricity when used in special environments can also create safety hazards. Due to the flammability of textile materials, it can cause fires in serious cases, causing losses to people's lives and property safety.
[0004] Therefore, in actual use, people often process textile materials. A common processing method is to prepare a textile finishing agent, directly immerse the textile or apply it on the surface of the textile to form a functional coating. For example, the patent with announcement number CN112267306B discloses a flame retardant and antistatic fabric and a preparation method thereof. The flame retardant and antistatic fabric includes a fabric layer and a functional coating. Modified carbon nanotubes and flame retardants are added to the functional coating to achieve flame retardant and antistatic properties of the fabric. However, the coating of this fabric is easily washed off during long-term washing and use, resulting in the loss of flame retardant and antistatic capabilities, affecting the service life of the product. Summary of the invention
[0005] The purpose of the present invention is to provide a highly weather-resistant textile material and a preparation method thereof, which solves the following technical problems: (1) the problem that ordinary textile materials have poor antistatic and flame retardant properties; (2) the problem that ordinary textile materials have poor resistance to ultraviolet aging and wet heat aging, short service life and no antibacterial ability.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A highly weather-resistant textile material, wherein the highly weather-resistant textile material is made by mixing aging-resistant ramie fiber and flame-retardant modified polyester fiber; The anti-aging kenaf fiber is prepared by reacting modified kenaf fiber with vanillic acid; the modified kenaf fiber is prepared by reacting kenaf fiber with epichlorohydrin after alkali treatment; The flame-retardant modified polyester fiber is prepared by melt spinning polyethylene terephthalate and a flame-retardant composite; the flame-retardant composite is prepared by forming a nitrogen-phosphorus flame retardant on the surface of nano zinc oxide.
[0007] Furthermore, the aging-resistant kenaf fiber comprises the following preparation steps: S1: soaking kenaf fiber in sodium hydroxide solution for 1-1.5 hours, taking it out, washing and drying it, placing it in deionized water, swelling it at room temperature for 30-35 minutes, adding epichlorohydrin and potassium carbonate, heating it to 45-55° C. and stirring it for 3-5 hours, filtering, washing and drying it to obtain modified kenaf fiber; S2: placing the modified kenaf fiber in N,N-dimethylformamide, adding vanillic acid and a catalyst, heating to 85-95°C for reaction for 5-6 hours, filtering, washing and drying to obtain the aging-resistant kenaf fiber.
[0008] In this scheme, the hydroxyl groups on the surface of the kenaf fiber are activated after being treated with alkali, and react with the active chlorine in the epichlorohydrin structure under the action of potassium carbonate to obtain a modified kenaf fiber containing epoxy groups on the surface. Then, under the action of a catalyst, the epoxy groups in the modified kenaf fiber structure undergo a ring-opening reaction with the carboxyl groups in the vanillic acid structure to obtain an aging-resistant kenaf fiber. The anti-aging kenaf fiber uses kenaf fiber as a matrix material. The kenaf fiber has good air permeability and can enhance the comfort of the textile material. At the same time, multiple active hydroxyl groups are formed on its surface, which can form an adsorption effect with the surface of the flame-retardant modified fiber with a positive charge. When the textile material is actually used, the compactness of the material can be enhanced to improve the mechanical strength, so that the structure is not easy to loosen during washing and pulling, the durability of the textile material is improved, and it is not easy to deform when used for a long time. At the same time, vanillic acid is introduced into its surface in a chemically bonded manner. Vanillic acid can remove free radicals and slow down or prevent free radical chain reactions by reacting with free radicals, thereby improving the aging resistance of the textile material. The vanillic acid introduced in this way is not easy to precipitate, has a long-lasting antioxidant effect, and can effectively improve the service life of the textile material.
[0009] Furthermore, in step S1, the mass fraction of the sodium hydroxide solution is 8-10%.
[0010] Furthermore, in step S2, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, and tetrabutylammonium hydroxide.
[0011] Furthermore, the flame retardant modified polyester fiber comprises the following preparation steps: (1) Place nano zinc oxide in deionized water, ultrasonically disperse for 10-15 minutes, add 2,6-pyridinedicarbonyl chloride, mix well, heat to 70-80°C and stir for 8-10 hours. After the mixture is separated, the solid is washed and dried to obtain modified nano zinc oxide; (2) placing the modified nano zinc oxide in acetone, ultrasonically dispersing for 15-20 minutes, adding di-tert-butyl chloromethyl phosphate, heating and refluxing, filtering, washing, and drying to obtain a flame retardant composite; (3) Mixing polyethylene terephthalate and the flame retardant compound and stirring them uniformly, placing them in a twin-screw extruder, setting the screw speed to 300-500 r / min, the temperature of each zone to 240-250°C, 250-260°C, 270-280°C, 280-285°C, and 270-275°C, melt-extruding and granulating, and slicing them after cooling to obtain a mixed material; (4) The mixed material is placed in the barrel of a melt spinning machine, compacted with a press rod, and melt-spinned. After natural cooling, the mixed material is placed in 55-60° C. water, stretched 8-10 times, and then dried to obtain flame-retardant modified polyester fiber.
[0012] In this scheme, the acyl chloride group in the 2,6-pyridinedicarboxylic acid chloride structure interacts with the hydroxyl group on the surface of nano zinc oxide to obtain modified nano zinc oxide, and then through a temperature rise reflux reaction, the pyridine ring on the surface of the modified nano zinc oxide can react with the active chlorine in the di-tert-butyl chloromethyl phosphate structure to undergo a quaternization reaction to obtain a flame retardant composite. The flame retardant composite uses nano zinc oxide as a matrix material and has good anti-ultraviolet and antibacterial capabilities. A nitrogen-phosphorus synergistic flame retardant is formed on its surface to give it an excellent flame retardant effect. The flame retardant composite is mixed with polyethylene terephthalate and melt-extruded, and then a flame retardant modified polyester fiber is obtained by a melt spinning method. The flame retardant modified polyester fiber has a quaternary ammonium structure on its surface, which can further improve the antibacterial properties of the textile material and give the textile material the ability to resist ultraviolet rays. When a fire occurs, it can exert an excellent flame retardant effect, thereby effectively expanding the use field of the textile material and enhancing its safety in use.
[0013] Furthermore, in step (1), the particle size of the nano zinc oxide is 50-100 nm.
[0014] Furthermore, in step (2), the temperature rising and reflux reaction time is 6-8h.
[0015] Furthermore, in step (4), the temperature of the melt spinning is 230-240°C.
[0016] A method for preparing a highly weather-resistant textile material, the method for preparing the highly weather-resistant textile material comprising: The aging-resistant kenaf fiber is blended with the flame-retardant modified polyester fiber to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0017] Furthermore, the mass ratio of the aging-resistant kenaf fiber to the flame-retardant modified polyester fiber is 2-5:3-10.
[0018] Beneficial effects of the present invention: The present invention prepares aging-resistant kenaf fiber and flame-retardant modified polyester fiber for mixed spinning, so that the prepared textile material has excellent and long-lasting ultraviolet resistance, aging resistance, flame retardancy and antibacterial effect, can effectively resist ultraviolet erosion and aging in a hot and humid environment, and significantly improves the service life of the textile material. At the same time, it can also play an excellent flame retardant effect when a fire occurs, has high safety in use, and also has an antibacterial effect, is not easy to mildew, and can effectively improve the storage stability of the textile material.
[0019] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0021] Figure 1 This is the zeta potential diagram of the modified nano zinc oxide and flame retardant composite in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1 1. Preparation of aging-resistant kenaf fiber S1: 15g of kenaf fiber was soaked in 60ml of 8% sodium hydroxide solution for 1h, taken out, washed and dried, placed in 80ml of deionized water, swollen at room temperature for 30min, 10g of epichlorohydrin and 1g of potassium carbonate were added, the temperature was raised to 45℃ and stirred for 3h, filtered, washed and dried to obtain modified kenaf fiber; The content of epoxy groups in the modified kenaf fiber was determined by the hydrochloric acid pyridine method. 2g of modified kenaf fiber was weighed as a sample, 20ml of hydrochloric acid-pyridine solution was added, heated to reflux for 0.5h, cooled to room temperature, 10ml of neutral acetone was added for rinsing, 2 drops of phenolphthalein indicator were added, and titrated with 0.5mol sodium hydroxide ethanol standard solution until the solution changed color to stop the reaction, and a blank test was performed at the same time; the content of epoxy groups in the sample was calculated by referring to the following formula: Epoxy group content (%) = (V-V0)c / 1000m; where V is the volume of sodium hydroxide ethanol standard solution consumed when titrating the sample solution, ml; V0 is the volume of sodium hydroxide ethanol standard solution consumed in the blank experiment, ml; c is the concentration of sodium hydroxide ethanol standard solution, mol / L; m is the sample mass, g; the content of epoxy groups in the modified kenaf fiber was calculated to be 8.6%; S2: 18 g of modified kenaf fiber was placed in 100 ml of N,N-dimethylformamide, 6 g of vanillic acid and 0.5 g of tetrabutylammonium bromide were added, the temperature was raised to 85° C. and reacted for 5 h. After filtering, washing and drying, the aging-resistant kenaf fiber was obtained.
[0024] The content of epoxy groups in the aging-resistant kenaf fiber was tested by the hydrochloric acid pyridine method. The specific operation method was the same as step S1. After calculation, the content of epoxy groups in the aging-resistant kenaf fiber was 0.7%. Compared with the modified kenaf fiber, the content of epoxy groups in the aging-resistant kenaf fiber was significantly reduced. This was due to the consumption of epoxy groups in the modified kenaf fiber structure reacting with the carboxyl groups in the vanillic acid structure.
[0025] 2. Preparation of flame retardant modified polyester fiber (1) 3 g of nano zinc oxide with a particle size of 50 nm was placed in 80 ml of deionized water, and after ultrasonic dispersion for 10 min, 2.2 g of 2,6-pyridinedicarbonyl chloride was added, mixed evenly, heated to 70 ° C and stirred for 8 h. After the end, the solid was separated, washed and dried to obtain modified nano zinc oxide; (2) 3.5 g of modified nano zinc oxide was placed in 100 ml of acetone, and after ultrasonic dispersion for 15 min, 3 g of di-tert-butyl chloromethyl phosphate was added, and the temperature was raised to reflux for 6 h. After filtering, washing, and drying, a flame retardant composite was obtained; The zeta potential value of modified nano zinc oxide and flame retardant composites was tested using ZPA20 zeta potential analyzer. Figure 1It can be seen that the potential value of modified nano zinc oxide is -2.6mv; the potential value of the flame retardant composite is 3.8mv; it can be seen that the surface of modified nano zinc oxide has a negative charge because the hydroxyl groups on its surface are negatively charged, while the surface of the flame retardant composite has a positive charge because the positively charged quaternary ammonium groups are generated in the structure of the flame retardant composite.
[0026] (3) 30 g of polyethylene terephthalate and 3.8 g of flame retardant compound were mixed and stirred evenly, placed in a twin-screw extruder, the screw speed was set to 300 r / min, the temperature of each zone was set to 240°C, 250°C, 270°C, 280°C, and 270°C, melt extruded into granules, and sliced after cooling to obtain a mixed material; (4) The mixed material is placed in the barrel of a melt spinning machine, compacted with a press rod, the temperature is set to 230°C, the spinning speed is set to 160 m / min, melt spinning is performed, and after natural cooling, the mixed material is placed in 55°C water, stretched 8 times, and then dried to obtain a flame-retardant modified polyester fiber.
[0027] 3. Preparation of Textile Materials 20 g of aging-resistant kenaf fiber and 30 g of flame-retardant modified polyester fiber are blended to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0028] Example 2 Preparation of textile materials 30g of aging-resistant kenaf fiber and 50g of flame-retardant modified polyester fiber are blended to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0029] The preparation method of the aging-resistant kenaf fiber and the flame-retardant modified polyester fiber is the same as that in Example 1.
[0030] Example 3 Preparation of textile materials 50g of aging-resistant kenaf fiber and 100g of flame-retardant modified polyester fiber are blended to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0031] The preparation method of the aging-resistant kenaf fiber and the flame-retardant modified polyester fiber is the same as that in Example 1.
[0032] Comparative Example 1 Preparation of textile materials 30 g of kenaf fiber and 50 g of flame-retardant modified polyester fiber are blended to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0033] The preparation method of the flame retardant modified polyester fiber is the same as that in Example 1.
[0034] Comparative Example 2 Preparation of textile materials (1) 30 g of polyethylene terephthalate was mixed and stirred uniformly, placed in a twin-screw extruder, the screw speed was set to 300 r / min, the temperatures of each zone were set to 240°C, 250°C, 270°C, 280°C, and 270°C, melt-extruded into granules, and sliced after cooling to obtain a mixed material; (2) placing the mixed material in the barrel of a melt spinning machine, compacting it with a press rod, setting the temperature to 230°C and the spinning speed to 160 m / min, performing melt spinning, cooling it naturally and placing it in 55°C water, stretching it 8 times and then drying it to obtain polyester fiber; (3) 30 g of aging-resistant kenaf fiber and 50 g of polyester fiber are blended to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0035] The method for preparing the aging-resistant kenaf fiber is the same as that in Example 1.
[0036] Comparative Example 3 Preparation of textile materials (1) 30 g of polyethylene terephthalate and 3.8 g of modified nano zinc oxide were mixed and stirred evenly, placed in a twin-screw extruder, the screw speed was set to 300 r / min, the temperatures of each zone were set to 240°C, 250°C, 270°C, 280°C, and 270°C, melt-extruded into granules, and sliced after cooling to obtain a mixed material; (2) placing the mixed material in the barrel of a melt spinning machine, compacting it with a press rod, setting the temperature to 230°C and the spinning speed to 160 m / min, performing melt spinning, and placing it in 55°C water after natural cooling, stretching it 8 times and then drying it to obtain modified polyester fiber; (3) 30 g of aging-resistant kenaf fiber and 50 g of modified polyester fiber are blended to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
[0037] The method for preparing the aging-resistant kenaf fiber is the same as that in Example 1.
[0038] Performance Testing The textile materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were cut into samples that met the specifications, and the antibacterial rate of the samples was calculated according to the standard GB / T20944.3-2008 to determine the antibacterial effect of the samples. The surface resistivity of the samples was tested using a DRK321B-II surface resistivity tester to determine their antistatic ability. The samples were placed in a UV aging box using a universal material testing machine at an ultraviolet wavelength of 313 nm and an irradiance of 0.72 / m 2 The samples after 24 hours of radiation and the samples after 24 hours of treatment at 100℃ were subjected to tensile property test; the mechanical strength, UV resistance and aging resistance of the samples were judged; the flame retardant grade of the samples was tested with reference to the UL-94 standard; the specific test results are shown in the table below: Antibacterial rate / % Surface resistance / Ω·m Tensile strength / MPa Tensile strength after UV irradiation / MPa Tensile strength after high temperature aging / MPa Flame retardant grade Example 1 99.5 <![CDATA[2.4×10 6 ]]> 1.85 1.56 1.66 V-0 Example 2 99.6 <![CDATA[1.6×10 6 ]]> 1.89 1.61 1.70 V-0 Example 3 99.3 <![CDATA[1.8×10 6 ]]> 1.87 1.59 1.69 V-0 Comparative Example 1 98.9 <![CDATA[2.7×10 6 ]]> 1.83 1.54 1.02 V-0 Comparative Example 2 62.3 <![CDATA[1.9×10 12 ]]> 1.80 1.05 1.59 V-2 Comparative Example 3 81.4 <![CDATA[1.4×10 12 ]]> 1.82 1.52 1.60 V-2 It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent antibacterial properties, antistatic properties, mechanical strength, anti-ultraviolet ability and aging resistance, and have excellent flame retardant effects. In the samples prepared in Comparative Example 1, unmodified kenaf fiber is directly used, and the aging resistance is poor. In the samples prepared in Comparative Example 2, polyethylene terephthalate is directly used to make unimproved polyester fiber, and the antibacterial property, anti-ultraviolet ability and flame retardant effect of the textile material prepared are poor. In the samples prepared in Comparative Example 3, modified polyester fiber is prepared by mixing modified nano zinc oxide with polyethylene terephthalate, and the textile material prepared has strong anti-ultraviolet ability and certain antibacterial properties, but poor antistatic effect and flame retardant properties.
[0039] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0040] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A highly weather-resistant textile material, characterized in that: The highly weather-resistant textile material is made by mixing aging-resistant kenaf fibers and flame-retardant modified polyester fibers; The anti-aging kenaf fiber is prepared by reacting modified kenaf fiber with vanillic acid; the modified kenaf fiber is prepared by reacting kenaf fiber with epichlorohydrin after alkali treatment; The flame-retardant modified polyester fiber is prepared by melt spinning polyethylene terephthalate and a flame-retardant composite; the flame-retardant composite is prepared by forming a nitrogen-phosphorus flame retardant on the surface of nano zinc oxide.
2. A highly weather-resistant textile material according to claim 1, characterized in that: The aging-resistant kenaf fiber comprises the following preparation steps: S1: soaking kenaf fiber in sodium hydroxide solution for 1-1.5 hours, taking it out, washing and drying it, placing it in deionized water, swelling it at room temperature for 30-35 minutes, adding epichlorohydrin and potassium carbonate, heating it to 45-55° C. and stirring it for 3-5 hours, filtering, washing and drying it to obtain modified kenaf fiber; S2: placing the modified kenaf fiber in N,N-dimethylformamide, adding vanillic acid and a catalyst, heating to 85-95°C for reaction for 5-6 hours, filtering, washing and drying to obtain the aging-resistant kenaf fiber.
3. A highly weather-resistant textile material according to claim 2, characterized in that: In step S1, the mass fraction of the sodium hydroxide solution is 8-10%.
4. A highly weather-resistant textile material according to claim 2, characterized in that: In step S2, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, and tetrabutylammonium hydroxide.
5. The highly weather-resistant textile material according to claim 1, characterized in that: The flame retardant modified polyester fiber comprises the following preparation steps: (1) Place nano zinc oxide in deionized water, ultrasonically disperse for 10-15 minutes, add 2,6-pyridinedicarbonyl chloride, mix well, heat to 70-80°C and stir for 8-10 hours. After the mixture is separated, the solid is washed and dried to obtain modified nano zinc oxide; (2) placing the modified nano zinc oxide in acetone, ultrasonically dispersing for 15-20 minutes, adding di-tert-butyl chloromethyl phosphate, heating and refluxing, filtering, washing, and drying to obtain a flame retardant composite; (3) Mixing polyethylene terephthalate and the flame retardant compound and stirring them uniformly, placing them in a twin-screw extruder, setting the screw speed to 300-500 r / min, the temperature of each zone to 240-250°C, 250-260°C, 270-280°C, 280-285°C, and 270-275°C, melt-extruding and granulating, and slicing them after cooling to obtain a mixed material; (4) The mixed material is placed in the barrel of a melt spinning machine, compacted with a press rod, and melt-spinned. After natural cooling, the mixed material is placed in 55-60° C. water, stretched 8-10 times, and then dried to obtain flame-retardant modified polyester fiber.
6. A highly weather-resistant textile material according to claim 5, characterized in that: In step (1), the particle size of the nano zinc oxide is 50-100 nm.
7. The highly weather-resistant textile material according to claim 5, characterized in that: In step (2), the temperature rising and reflux reaction time is 6-8h.
8. The highly weather-resistant textile material according to claim 5, characterized in that: In step (4), the temperature of the melt spinning is 230-240°C.
9. The method for preparing a highly weather-resistant textile material according to claim 1, characterized in that: The preparation method of the highly weather-resistant textile material is as follows: The aging-resistant kenaf fiber is blended with the flame-retardant modified polyester fiber to form yarn, and the yarn is woven using a plain weaving method to obtain a textile material.
10. The method for preparing a highly weather-resistant textile material according to claim 9, characterized in that: The mass ratio of the aging-resistant kenaf fiber to the flame-retardant modified polyester fiber is 2-5:3-10.
Citation Information
Patent Citations
A flame-retardant and antistatic fabric and its preparation method
CN112267306B